Pengaruh Pergaulan Teman Sebaya Terhadap Hasil Belajar Siswa Pada Pembelajaran PAI di SMP Negeri 1 Padang Gelugur - Saimatur Rohmah; Jasmienti J (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research was motivated by the discovery of problems related to peer interactions at SMP Negeri 1 Padang Gelugur in Islamic Education learning for class VIII students, such as often being late for class, working together on tests and cheating on tests, because they prefer to see the students' learning results. In contrast to studying alone, many students only study during exams and there are still students who have report cards that do not meet the Minimum Completion Criteria. Then we also found around 25% of students with scores equivalent to the Minimum Completion Criteria. Even though in delivering the material the teacher has presented the material in its entirety and in depth. Each student also has a textbook and companion book which is facilitated by the school. So this research aims to determine the influence of peer interactions on students' PAI learning outcomes and how big the influence is. The research used in this research is quantitative correlation research. The population was all class VIII students, totaling 129 students and the sample in this study used a purposive sampli ng technique and obtained 32 students as the sample. Data was collected through questionnaires and documentation with prerequisite test data analysis and simple linear regression Based on the results of research that has been carried out, the results obtained are that peer interaction has an influence on students' PAI learning outcomes as evidenced by the sig value of 0.045 ? 0.05 and the calculated t value ? t table, namely 2.077 ? 2.042. And peer interactions have an influence of 12.6% on students' PAI learning outcomes and the remainder is influenced by other factors not examined in this research.